Aktivitas Antihiperurisemia Ekstrak Etanol Daun Afrika (Vernonia amygdalina Delile.) pada Mencit Putih Galur Swiss Webster yang Diinduksi Melinjo dan Hati Ayam - Doni Anshar Nuari; Hesti Renggana; Cindra Tri Yuniar; Mentari Novitasari; Asholeha Lulu (Pharmacon: Jurnal Farmasi Indonesia, 2021)
Hyperuricemic is a condition in which uric acid level in blood exceeds its normal level. Empirically, African leaves (Vernonia amygdalina Delile.) were used to treat diabetic, hypercholesterolemic, fever, hypertension and hyperuricemic by drinking boiled water of African leaves. This in vivo study was performed to determine antihyperuricemic activity of ethanolic extract of African leaves on male mice using the POCT (Point of Care Testing) method. Suspension combination of melinjo and chicken liver juice were used as hyperuricemic inductor. It is given orally for consecutive 9 days and the uric acid level were tested on day 1, 3, 6, and 9. The results showed that the ethanolic extract of African leaves (Vernonia amygdalina Delile.) at dosage 100, 200, and 400 mg/KgBW had a significantly different antihyperuricemic activity against negative control.